Bioremoval of Contaminated in Wastewater by Using Alginate Immobilized Cell of Green Microalga Nannochloropsis oculata - Paweeporn Jongyingjaroenyod; Buppha Jongput; Suneerat Ruangsomboon (King Mongkut's Agricultural Journal, 2024)
The optimum conditions and adsorption kinetic for bioremoval of benefix red by immobilized cell of Nannochloropsis oculata were studied. The results showed that the optimum pH for bioremoval of dye was at 2 with the highest adsorption capacity of 0.90±0.01 mg/g. The equilibrium time of adsorption was 2 h with adsorption capacity of 1.80±0.02 mg/g. The optimum biomass was 2 g/l with adsorption capacity of 3.98±0.02 mg/g. The adsorption capacity (qeq) decreased when the algal biomass increased. The adsorption characteristics fitted well with the Langmuir adsorption isotherm with maximum adsorption capacity (Qmax) of 106.58±20.22 mg/g. Dye removal correlated with pseudo first-order, while the adsorption rate was limited by film and intraparticle diffusion at secondary step. It can be concluded that alginate immobilized cell of N. oculata may be used as an alternative for removal of benefix red contaminated in wastewater.
Keywords: Adsorption and biosorption for pollutant removal; Water Quality Monitoring and Analysis; Analytical chemistry methods development